Tata Kelola Dompet Digital di Indonesia dalam Perspektif Local Institution pada Global Value Chain Digital - Maghfiroh, Melati Ning; Kusuma, Arnold Arswenda (Universitas Islam Darul Ulum Lamongan, 2025)
The rise of digital wallets in Indonesia is a significant component of the nation's digital economic transformation and its growing involvement in global economic networks. This expansion is influenced not only by technological advancements and market dynamics but also by the influence of local institutions in regulating digital financial services. This research explores the governance of digital wallets in Indonesia through the lens of a digital Global Value Chain (GVC), concentrating on the roles of Bank Indonesia and the Financial Services Authority as domestic regulatory bodies. The study employs a qualitative analytical-descriptive method, utilizing secondary data gathered from regulatory documents, institutional reports, and pertinent academic literature. The data are examined using thematic qualitative analysis, with the digital GVC framework serving as a conceptual tool. The results reveal that the regulatory and supervisory frameworks established by Bank Indonesia and the Financial Services Authority act as governance mechanisms that facilitate Indonesia's integration into the global digital GVC. While these frameworks offer institutional certainty and create opportunities for functional advancement among local digital wallet providers, they also lead to market concentration and the potential perpetuation of hierarchical dependency within the digital GVC structure. In summary, the study underscores that the path of digital wallet development and the distribution of its economic benefits in Indonesia are heavily influenced by the design and capacity of local institutions.